Modeling the Relationships Between Metacognitive Beliefs, Attention Control and Symptoms in Children With and Without Anxiety Disorders: A Test of the S-REF Model - Reinholdt-Dunne, Marie Louise; Blicher, Andreas; Nordahl, Henrik; Normann, Nicoline; Esbjørn, Barbara Hoff; Wells, Adrian (Frontiers in Psychology, 2019)
The aim of the current study was to investigate the relative contribution of attention control and metacognitive beliefs to symptoms of anxiety and depression in children with anxiety disorders and in non-clinical controls. In the metacognitive model, these factors are part of a transdiagnostic syndrome contributing to disorder. In a cross-sectional design, 351 children (169 children diagnosed with a primary anxiety disorder and 182 community children) between 7 and 14 years of age completed self-report measures of symptoms, attention control and metacognitive beliefs. Clinically anxious children reported significantly higher levels of anxiety, lower levels of attention control and higher levels of maladaptive metacognitive beliefs than controls. Across groups, lower attention control and higher levels of maladaptive metacognitive beliefs were associated with stronger symptoms, and metacognitions were negatively associated with attention control. Domains of attention control and metacognitions explained unique variance in symptoms when these were entered in the same model within groups, and an interaction effect between metacognitions and attention control was found in the community group that explained additional variance in symptoms. In conclusion, metacognitive knowledge and individual differences in attention control both contributed to psychological dysfunction in children, and metacognitions appeared to be the strongest factor.